Feasibility and acceptability of GeneXpert MTB/XDR implementation among healthcare workers in three low-middle income African countries. - Sara Keller; Kogieleum Naidoo; Medhane Zekarias; Sussan Israel-Isah; Mohammed Shaka; Gcinile Gule; Anushka Naidoo; Miriam Bathnna; Judith Nomthandazo Dlamini-Miti; Kalkidan Yae; Evaezi Okpokoro; Alash'le Abimiku; et al. (PLoS ONE)
Background Xpert MTB/XDR (Xpert-XDR) testing can significantly shorten time to initiating appropriate drug-resistant tuberculosis (DR-TB) treatment, but its introduction may impact laboratory workflow, especially in laboratories not currently performing drug susceptibility testing. This study evaluated the feasibility and acceptability of implementing the Xpert-XDR for rapid triage and selection of all-oral regimens for DR-TB. Method This was a multi-country, multi-site qualitative study conducted between July and November 2023, as part of the larger TriAD (Triage test for All oral DR TB drugs) study implemented in South Africa, Ethiopia, and Nigeria. We conducted semi-structured in-depth interviews with clinicians, nurses and laboratory staff at each study site until thematic saturation was achieved. Additionally, we interviewed policy makers (n = 9) and people with TB (PWTB) (n = 11), to provide additional insight on the implementation of this new diagnostic assay. Results Healthcare workers (n = 61) found the new workflow feasible and acceptable. It was the increased speed in which PWTB would receive a correct diagnosis and appropriate treatment that provided the biggest benefit to moving to Xpert-XDR for healthcare workers and PWTB. Laboratory staff mentioned that Xpert-XDR had expedited and simplified the laboratory workflows. Role-appropriate and ongoing training is a key factor in effective implementation as described by policy makers and healthcare workers alike. Barriers impacting the ability to perform Xpert-XDR included unstable power supply, internet, and temperature control. Additionally, the Xpert MTB/Rif Ultra test has higher sensitivity for the detection of TB than the Xpert-XDR test, leading to discordant test results. Conclusion This study showed that implementation of Xpert-XDR in health facilities is both feasible and acceptable by all types of healthcare workers. Some barriers with Xpert-XDR are not exclusive to this particular diagnostic tool but are important to address when policy makers are deciding which tools to implement.